2000
DOI: 10.1159/000064858
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy of Imipramine with Oxybutynin in Children with Enuresis Nocturna

Abstract: Purpose: The treatment approach for enuresis is controversial due to the lack of consensus as to the exact causes of nocturnal enuresis. Despite various treatment modalities, pharmacotherapy still appears to be the common choice. The aim of this prospective study was the evaluation of the efficacy of combination therapy (imipramine and oxybutynin) in patients with enuresis nocturna. Patients and Methods: This prospective study was done with 77 monosymptomatic nocturnal enuretics between July 1996 and December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Our study like the previous ones used combined imipramine with anticholinergic (oxybutynin), reported that combined therapy was more effective in MNE. 19,20 We used a low dose (25 mg) of imipramine in order to avoid its potential side effects and to combine it with the synergistic anticholinergic action of solifenacin. We did not assess the nocturnal urine production to increase patient’s compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Our study like the previous ones used combined imipramine with anticholinergic (oxybutynin), reported that combined therapy was more effective in MNE. 19,20 We used a low dose (25 mg) of imipramine in order to avoid its potential side effects and to combine it with the synergistic anticholinergic action of solifenacin. We did not assess the nocturnal urine production to increase patient’s compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Combination therapy including imipramine and anticholinergics showed improved results when compared to imipramine alone or placebo in the short and long term, with fewer relapses than imipramine monotherapy (54, 58). The combination of tricyclic antidepressants and desmopressin did not show any improvement in treatment results (54, 59).…”
Section: Other Drugsmentioning
confidence: 97%
“…To our knowledge, there is only one report of a combined therapy using a tricyclic antidepressant with an anticholinergic agent which has been published recently [8]. This is surprising since each drug type appears to have a different effect on urinary bladder function.…”
Section: Introductionmentioning
confidence: 99%